Removal of red 2 and yellow 6 by Zn- and-Na modified zeolitic tuffs in the presence of H2O2. Issue 35 (26th July 2016) - Salazar-Gil, K.; Díaz-Nava, M.C.; Solache-Ríos, M.
Abstract: The adsorption of red-2 and yellow-2 dyes from aqueous solution was evaluated using both Na and Zn zeolitic materials in the absence and presence of hydrogen peroxide. The adsorbents were characterized by scanning electron microscopy, X-ray diffraction, and their specific surface areas were determined. Sorption kinetic and isotherms, in the absence and presence of hydrogen peroxide, were determined. The kinetic adsorption behavior of red-2 and yellow-2 by Na-zeolitic tuff and in presence of H2 O2 was similar. The experimental data of the adsorption of red-2 were best adjusted to the kinetic model of Lagergren and the data of yellow-6 to the pseudo-second-order model indicating chemisorption. The adsorption isotherms in the absence of H2 O2 showed low adsorption capacities, however sodium zeolitic tuff in the presence of hydrogen peroxide showed to be an efficient material for the removal of these dyes.